1983
DOI: 10.1159/000234856
|View full text |Cite
|
Sign up to set email alerts
|

Search for Thymocyte Growth-Stimulating Activity in Extracts of Different Tissues and among Established Growth Factors and Thymic Maturation Hormones

Abstract: A thymocyte specific growth factor has previously been prepared from calf thymus. Similar activity is now shown to be present in thymus and spleen of guinea pigs, but not in lymph nodes, liver and kidney. Purified thymic maturation hormones, interleukins and several growth factors for other cell types than lymphocytes were tested and found not to stimulate DNA synthesis of thymocytes. A slight activity was found in thymosin fraction 5, known to contain at least 35 polypeptides. Our factor lacked comitogenic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Our data do not indicate any chemical relationship with chemically defined thymic differentiation hor mones [3 for discussion] or established growth factors [9] , a concept further supported by functional studies [10] . Studies of amino acid composition, N-terminalblocking moiety and digestion with carboxypeptidase Y are in progress.…”
Section: Further Characterizationsupporting
confidence: 51%
“…Our data do not indicate any chemical relationship with chemically defined thymic differentiation hor mones [3 for discussion] or established growth factors [9] , a concept further supported by functional studies [10] . Studies of amino acid composition, N-terminalblocking moiety and digestion with carboxypeptidase Y are in progress.…”
Section: Further Characterizationsupporting
confidence: 51%
“…Interleukin-2 Assay IL-2 activity was determined by utilizing IL-2-dependent rat lymphoblasts obtained from primary cultures of concanavalin A (Con A) activated splenic lymphocytes, essentially as described previously [14,15]. An IL-2 standard, used as a positive control, was prepared from the conditioned medium of Con A-Sepharosestimulated spleen cells [ 14], Thymocyte Growth Peptide Assay TGP activity was evaluated by measuring the recruitment from G, into S phase of guinea pig thymocytes in short-term cultures [10].…”
Section: Lymphocyte Culturesmentioning
confidence: 99%
“…In previous papers, we have reported on the biochemical and functional properties of a thymic factor with ability to induce DNA synthesis specifically in immunologically in competent immature thymocytes [3][4][5]. The factor was shown to be biochemically and functionally distinct from other lymphocyte growth factors and from thymic differentiation hormones [6,7]. Kinetic studies showed that the thymic factor stimulated DNA syn thesis with a peak effect 4-8 h after start of culture [4,5], indicating that the target cells were Gl thymocytes which were influenced to initiate DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%